2020
DOI: 10.1093/europace/euaa103
|View full text |Cite|
|
Sign up to set email alerts
|

Results of the Patient-Related Outcomes of Mechanical lead Extraction Techniques (PROMET) study: a multicentre retrospective study on advanced mechanical lead extraction techniques

Abstract: Abstract Aims Several large studies have documented the outcome of transvenous lead extraction (TLE), focusing on laser and mechanical methods. To date there has been no large series addressing the results obtained with rotational lead extraction tools. This retrospective multicentre study was designed to investigate the outcomes of mechanical and rotational techniques. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
105
6
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(140 citation statements)
references
References 18 publications
22
105
6
7
Order By: Relevance
“…Evolution ® system has been associated with excellent clinical and procedural success with low complication rates in previous studies. [9][10][11] In our study, complete clinical success and procedural successes were 99.2% and 94.0%, respectively, as in other studies, complete clinical and procedural success rates have been mostly >95%. 8,11 The clinical and procedural success rates were 88.0% and 84.2% without using rescue methods in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Evolution ® system has been associated with excellent clinical and procedural success with low complication rates in previous studies. [9][10][11] In our study, complete clinical success and procedural successes were 99.2% and 94.0%, respectively, as in other studies, complete clinical and procedural success rates have been mostly >95%. 8,11 The clinical and procedural success rates were 88.0% and 84.2% without using rescue methods in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Our TLE outcome was also comparable to a recently published European registry, the PROMET (Patient-Related Outcomes of Mechanical lead Extraction Techniques) study, which was focused on the use of rotational TLE tools in 6 high-volume centers [22]. In the PROMET study, clinical success was obtained in [23].…”
Section: Liberal Combined Superior and Femoral Approachsupporting
confidence: 71%
“…Furthermore, our results are comparable to previously published studies using mechanical rotational sheaths. The reported major complication rates were between 0% and 1.5% 23–26 . Despite the advanced age of our patient population and the long lead dwell time, the procedure was safe, with comparable complication rates to younger populations.…”
Section: Discussionmentioning
confidence: 70%
“…Procedural success rates, ranging between 90% and 100% 7–11 have been described in previously published laser lead extraction studies analyzing younger populations. Studies using mechanical rotational sheaths have reported procedural success rates between 80% and 98.3% 23–26 …”
Section: Discussionmentioning
confidence: 99%